The Role of Business Ethics and Azarine Brand Popularity in Building Consumer Trust - Nura, Alfi; Br. Hutagalung, Natasya Dinda Putri; Pratiwi, Dinda; Auni, Meisya Syahinda; Shaliha, Aura Afifah; Simanihuruk, Raynata Timothy; Marbun, Ridu (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study investigates the interplay between business ethics and brand popularity in shaping consumer trust, focusing on the Azarine brand within the beauty industry. Maintaining consumer trust is vital for business development and sustainability in an increasingly competitive market. Business ethics encompasses principles such as transparency, honesty, and corporate responsibility, which are crucial for fostering consumer trust. The research highlights a recent incident involving Azarine, where allegations of over-claiming product efficacy led to significant consumer skepticism, despite the brand's strong market presence. Through a qualitative approach, data were collected from students at the Faculty of Economics, Universitas Negeri Medan, via questionnaires designed to elicit opinions on the impact of business ethics and brand popularity on consumer trust. The findings indicate that while brand popularity can attract initial consumer interest, long-term trust heavily relies on ethical practices and product quality. Respondents unanimously agreed that adherence to ethical standards is fundamental in building and maintaining consumer trust, particularly in the beauty sector where product claims directly impact health and safety. The study reveals that ethical violations, such as misleading product claims, can severely damage consumer confidence. Many respondents indicated they would discontinue using Azarine products due to the over-claim incident, viewing transparency and honesty as essential criteria for selecting beauty products. However, a small number expressed willingness to give the brand a second chance, contingent upon Azarine taking responsibility for its actions and improving transparency in its communications. Conversely, while brand popularity can serve as an initial draw, the study concludes that it is insufficient to sustain consumer trust in the face of ethical breaches. Respondents noted a decline in Azarine's popularity following the incident, emphasizing that a brand’s reputation is not solely built on recognition but also on ethical integrity. Ultimately, this research underscores the necessity for brands like Azarine to enhance their ethical standards and transparency to rebuild consumer trust and maintain a competitive edge. Recommendations for future research include exploring the relationship between product quality, innovation, and consumer trust in greater depth. By understanding these dynamics, companies can develop more effective strategies that align ethical practices with consumer expectations, thereby fostering long-term relationships built on trust and credibility